The relationship between authentic leaders and employees’ creativity. What are the roles of affective commitment and job resourcefulness? - Semedo, Ana Suzete (2018)
Purpose The purpose of this study is to investigate how authentic leadership (AL) predicts creativity both directly and through the mediating role of affective commitment (AC) and job resourcefulness (JR). Design/methodology/approach Data collected from a questionnaire administered to a sample of five hundred forty-three employees has been analysed. The model was tested using structural equation modelling. Findings The findings show that AL predicts AC, JR and creativity. The findings also show that AC and JR predict creativity. In other words, leaders’ authenticity increases employees’ creative spirit and thus, employees’ ability to overcome obstacles and meet challenges at work and their emotional bond play an important role (mediators) in this relationship. Practical implications The results of this study are conclusive and contribute to a better understanding of AL and its implication for employees’ emotional bond, their ability to overcome obstacles and their ability to introduce new and useful ideas. This study provides evidence that organizations should focus on training leaders with authentic characteristics. Originality/value This study considers both AC and JR as mediators of the relationship between AL and creativity. Therefore, the originality of this study lies in the integration of these four concepts in a single study to provide a model that depicts the chain of effects between AL, AC, JR and an employee’s creativity.